Navigating financial challenges: a case study on E.Gen Consultants Ltd. - theoretical insights and strategic recommendations - Islam, Shanta (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.